2018
DOI: 10.3389/fphar.2018.01424
|View full text |Cite
|
Sign up to set email alerts
|

Pimavanserin and Lorcaserin Attenuate Measures of Binge Eating in Male Sprague-Dawley Rats

Abstract: Binge eating disorder (BED) is characterized by dysregulated feeding and reward-related processes, and treatment is often challenged by limited therapeutic options. The serotonin (5-HT) 5-HT2A receptor (5-HT2AR) and 5-HT2CR are implicated in both feeding-related and reward-related behaviors and are thus poised to regulate BED-related behaviors. The purpose of this study was to assess the efficacy of the FDA-approved medications pimavanserin, a 5-HT2AR antagonist/inverse agonist, and lorcaserin, a 5-HT2CR agoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…In this study mCPP also decreased BOLD fMRI responses to the sight of food pictures in areas of reward-associated circuitry which is consistent with preclinical evidence for a role of 5-HT2C receptors in drug reward (Fletcher et al, 2010;Higgins & Fletcher, 2003. Interestingly, lorcaserin was reported to decrease binge eating of high-fat food in rats and mice, an action which has been proposed to be mediated by a serotonin and dopamine neural reward circuit in the midbrain (Price et al, 2018;Xu et al, 2017). It has been proposed that patients with BED may consume excessive food at least in part due to disrupted satiety signals (Sysko et al, 2007), suggesting that a 5-HT2C receptor agonist could decrease food intake during a binge-eating episode by enhancing satiety.…”
Section: Pharmacological Mechanismssupporting
confidence: 88%
See 2 more Smart Citations
“…In this study mCPP also decreased BOLD fMRI responses to the sight of food pictures in areas of reward-associated circuitry which is consistent with preclinical evidence for a role of 5-HT2C receptors in drug reward (Fletcher et al, 2010;Higgins & Fletcher, 2003. Interestingly, lorcaserin was reported to decrease binge eating of high-fat food in rats and mice, an action which has been proposed to be mediated by a serotonin and dopamine neural reward circuit in the midbrain (Price et al, 2018;Xu et al, 2017). It has been proposed that patients with BED may consume excessive food at least in part due to disrupted satiety signals (Sysko et al, 2007), suggesting that a 5-HT2C receptor agonist could decrease food intake during a binge-eating episode by enhancing satiety.…”
Section: Pharmacological Mechanismssupporting
confidence: 88%
“…5-HT2C receptor activation attenuates reward-related behaviours such as drug-seeking and drug-taking (Fletcher et al, 2010;Higgins & Fletcher, 2003 and may therefore decrease palatable food intake by restoring normal reward-related behaviour (Thomas et al, 2018). Thus, it has been suggested (Price et al, 2018) that selective 5-HT2C receptor agonists could be effective in treating BED but to date no clinical trials have been reported. Similarly, to the best of our knowledge, there have been no 5-HT receptor antagonist studies conducted to investigate the potential contribution of LDX-induced serotonin release to the therapeutic actions of the drug in BED.…”
Section: Pharmacological Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of lorcaserin on food intake has been examined in different animal models of obesity. Some authors used a regular diet [ 60 , 61 ], and other investigators evaluated lorcaserin in rats maintained on a high-fat diet [ 36 , 62 , 63 ]. Lorcaserin treatment rats (1–2 mg/kg) reduced the percentage of body weight by selective reduction of body fat mass [ 36 , 60 ].…”
Section: 5-ht 2c Receptor Agonists In Control Over...mentioning
confidence: 99%
“…The 5-HT 2C agonist, lorcaserin, has shown efficacy in various substance use disorder models. Lorcaserin and the 5-HT 2A antagonist/inverse agonist, pimavanserin, were evaluated in a rat model of bingeing ( Price et al, 2018 ). Both drugs produced small reductions in palatable food intake, but not binge-frequency.…”
Section: Research Directions Into New Drugs To Treat Binge-eating Dis...mentioning
confidence: 99%